Strengthening Communities of Earthquake Victims through a Sanitation Program (Installation/Clean Water Supply and Portable MCK in Kampung Tugu Rw 3 Cibeureum Village, Cugenang, Cianjur) - Elferida Sormin; Ulinata; Sudarno P. Tampubolon; Haposan Sahala Raja Sinaga (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community Service Incentive Program Community Service Integrated with Freedom to Learn Campus Freedom Based on Key Performance Indicators for 2022 entitled Strengthening Communities for Earthquake Disaster Victims through the Sanitation Program (Procurement of Clean Water and Portable MCK in Kampung Tugu Rw 3 Cibeureum Village, Cugenang, Cianjur) that held from 12th-17th December 2022. This activity aims to ensure the availability of clean water and MCK in tents of residents'. The method used is a descriptive analysis with doing observations, installing water pipes, water pumping machines and MCK, digging, casting the foundation of the water tower scaffolding, assembling and welding the water tower scaffolding then make installation. The results show that clean water and MCK are available and can be used.